Penentuan Komoditas Unggulan Perikanan Tangkap di Perairan Provinsi Kepulauan Bangka Belitung - Dersi Herka Mayu; Dian Wijayanto; Abdul Kohar Mudzakir; Kurniawan Kurniawan (Bogor Agricultural University, 2021)
consisting of 954 islands with 218.236 tonnes capture fisheries potential. As a leading economic sector in the region, capture fisheries should be maintained sustainably. One of actions that can be done is focusing fisheries development on prime commodities. Purpose of this study were to identify prime commodities and potential commodities in Bangka Belitung waters. Location Quotient (LQ) Analysis, Shift Share (SS), and Specialization Index (SI) were used for data analysis. The result showed that there were three prime commodities i.e., red snapper (Lutjanus campecanus), mackerel (Scomberomorus commerson), and blue swimming crab (Portunus pelagicus). Other potential fisheries commodities in Bangka Belitung Province were grouper (Plectropomus leopardus), yellowtail (Caesio erythrogaster), sea catfish (Arius thalassinus), fork-tailed threadfin bream (Nemipterus furcocus), stingray (Dasyatis sp), and crab (Scylla serrata). Keywords: Bangka Belitung Province, capture fisheries, prime commodities